STUDY OF WORK CONDITIONS AS A FACTOR IN STRESS IN SEWING INDUSTRY WORKERS. - Irena Stoilova; Silvia Tzvetkova; Penka Stefanova (Peytchinski Publishing, 2015)
Sewing production is traditionally well developed in Bulgaria. With the development of production and technical progress, new health problems for workers appear. The aim of this study was to clarify the role of work conditions as a factor in the occurrence of stress in sewing industry workers. Subject of the study are 70 persons, employed in small and medium enterprises. Conclusions are made and recommendations given for improvement of the work conditions and psycho-climate.